Fraud:Faktor-Faktor Yang Mempengaruhi Dalam Pemahaman Mahasiswa Akuntansi - Hermelinda, Tuti; Rajagukguk, Thetty Surienty; Afriansyah, Berlian (Universitas Muhammadiyah Metro, 2024)
This research examines the extent to which the influence of Idealism and Love of Money influences a person's tendency to commit fraudulent acts in accounting or fraud. The respondents in this study were students of the Accounting Study Program who had taken Auditing 1 and 2 courses. The analytical tool used was multiple linear regression with the help of SPSS. The test tool used is partial and simultaneous hypothesis testing using the t test and F test. Data collection uses a 1-5 Likert scale questionnaire. The results of the hypothesis test show that the variables Idealism and Love of Money have both simultaneous and partial effects on Fraud. With the significant influence of the variables Idealism and Love of Money on fraud in accounting, it is necessary to have maximum understanding of the possibility of fraud, especially by financial managers, either directly or indirectly, which must be followed by sanctions that provide a long-term deterrent effect.